Synthesis of chalcone-based six and seven membered heterocyclic compounds and their biological activities against H1N1 virus / Marzieh Yaeghoobi - Yaeghoobi, Marzieh (2012)
This thesis describes the synthesis of a library of chalcones and several flavanones and 1,5-benzothiazepines derived from chalcones and some biological studies of these compounds against neuraminidase (NA). The environmentally benign one-pot method using PMA/SiO2 in ethanol has successfully been applied toward the preparation of flavanone analogues from 2¢- hydroxychalcones, 2¢-aminochalcones and 2¢-mercaptochalcones in reasonable yields. Reactions were screened in a variety of parameters, including solvents, temperatures, reaction time and amount of catalyst used. The nature of the solvent played a key role in the reaction where the reaction performed well in a polar protic solvent such as ethanol and only moderately in a polar aprotic solvent like acetonitrile. The reactions also seemed to be temperature dependent resulting a significant improvement in the yeild. All the reactions occurred smoothly in 1 mol% PMA-SiO2 in ethanol. The reaction times varied from 8.5-22 hrs depending upon the type of chalcone. Mono and dicationic ionic liquids (ILs) were employed as reusable catalysts for the synthesis of synthesize 1,5- benzothiazepines from chalcones and orthoaminothiophenol (o-ATP) in reasonable quantities. The counter ion was observed to influence the reaction time as well as yield of the reaction by effecting in the acidity of ILs. Better yields of 1,5- benzothiazepines were obtained in more acidic ILs. Amongst all 1,5-benzothiazepines synthesized, 4-(4-methoxyphenyl)-2-(naphthalen-2- yl)2,3dihydrobenzo[b][1,4]thiazepine,MA12, was transformed to 3-(4-methoxyphenyl)- 2-(naphthalen-2-ylmethyl)-2H-benzo[b][1,4]thiazine, 6MR during column purification. The conversion of seven-membered ring, thiazepine to six-membered ring, thiazine is proposed to occure through a naphthyl shift or hydrogen shift. The synthesized compounds (chalcones, flavanones and 1,5-benzothiaepines) were then investigated for their potency as NA inhibitors. Chalcones are shown to have some kind of activity as NA inhibitors. Quantitative structure-activity relationships for the chalcone compounds with the aid of 2D and 3D-QSAR models have been also studied. Flavanones and 1,5-benzothiazepines with promising Cdocker energy (compared to DANA with Cdocker interaction energy equal to -46.11 kcal/mol), were expected to be active against neuraminidase. However, the bioassay results were not corroborate with the modeling results. This observation presumably is due to the flavanones binding at the allosteric sites rather than the active site, the larger size of the seven-membered ring, lack of flexibility and solubility of 1,5-benzothiazepines.